Aptamer-Based Potentiometric Measurements of Proteins Using Ion-Selective Microelectrodes - Numnuam, A.; Chumbimuni-Torres, K.; Xiang, Y.; Bash, R.; Thavarungkul, P.; Kanatharana, P.; Pretsch, E.; Wang, J.; Bakker, Eric (American Chemical Society, 2008)
We here report on the first example of an aptamer-based potentiometric sandwich assay of proteins. The measurements are based on CdS quantum dot labels of the secondary aptamer, which were determined with a novel solid-contact Cd2+-selective polymer membrane electrode after dissolution with hydrogen peroxide. The electrode exhibited cadmium ion detection limits of 100 pM in 100 mL samples and of 1 nM in 200 microwells, using a calcium-selective electrode as a pseudoreference electrode. As a prototype example, thrombin was measured in 200 samples with a lower detection limit of 0.14 nM corresponding to 28 fmol of analyte. The results show great promise for the potentiometric determination of proteins at very low concentrations in microliter samples.